Immunocapture and microplate-based activity and quantity measurement of pyruvate dehydrogenase in human peripheral blood mononuclear cells. (March 2015) - Liu, Xiaowen; Pervez, Hira; Andersen, Lars W; Uber, Amy; Montissol, Sophia; Patel, Parth; Donnino, Michael W
Background: Pyruvate dehydrogenase (PDH) activity is altered in many human disorders. Current methods require tissue samples and yield inconsistent results. We describe a modified method for measuring PDH activity from isolated human peripheral blood mononuclear cells (PBMCs).Results/Methodology: We found that PDH activity and quantity can be successfully measured in human PBMCs. Freeze-thaw cycles cannot efficiently disrupt the mitochondrial membrane. Processing time of up to 20 h does not affect PDH activity with proteinase inhibitor addition and a detergent concentration of 3.3% showed maximum yield. Sample protein concentration is correlated to PDH activity and quantity in human PBMCs from healthy subjects.Conclusion: Measuring PDH activity from PBMCs is a novel, easy and less invasive way to further understand the role of PDH in human disease.